PENCIPTAAN LANGIT DAN BUMI DALAM Q.S. AL-ANBIYĀ’ [21] Ayat 30: Studi Ma’nā Cum Maghzā - Rahman, Muhammad Iqbal; Arifin, Syamsul; Tamsir, Tamsir; Darmadi, Darmadi; Hoir, Hubul (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2024)
This article will discuss comprehensively the creation of heaven and earth in Q.S. Al-Anbiyā' [21]: 30. This theme was raised because the surah describes the origins of the heavens and the earth. Interestingly, scientifically, human theories about the origin of the universe (including heaven and earth) emerged in the modern era through Nebula (1755), Big Bang (1927), Steady State Theory (1948), and others. Long before these theories emerged, the Al-Qur'ān through surah Al-Anbiyā': 30 said that heaven and earth were originally a unified form before being separated into heaven and earth. Therefore, this article will focus on the meaning of history, the main message of history, and the main dynamic message of Q.S. Al-Anbiyā' [21]: 30, and elaborates on the creation of heaven and earth based on scientific interpretation and approach. The method used in this paper is descriptive analysis. The approach used is contextual, where Ma'nā cum Maghzā is the theory. The results of this paper found that: (1) the historical meaning of surah Al-Anbiyā': 30 is a satire on unbelievers who do not want to believe even though they witness natural phenomena around them; (2) the main historical message is the importance of thinking about the creation of the heavens and the earth and being grateful for all the blessings that–originating from the air–God has given; (3) anyone who claims to believe in God should study not only religious knowledge but also study scientific knowledge. People who have the potential to make human life better, but do not do so, are considered infidels, that is, closing themselves off from the interests of living creatures.